Investigation of the interaction betweencoach transformational leadership andcoaching competency change over time - Kao, S.-F.; Tsai, C.-Y.; Schinke, R. (International Journal of Sports Science & Coaching, 2021)
Drawing on social cognitive theory, we examined a cross-level interaction between coach transformational leadership and the within-individual change in evaluations of perceived coaching competency over a season. We applied linear growth modeling to analyze 246 collegiate competitive basketball players (147 males and 99 females from 24 teams). Our results revealed that coaches with high transformational leadership were evaluated as having a decrease in perceived coaching competency over time. In contrast, coaches with low transformational leadership were evaluated as having an increase in perceived coaching competency over time. Implications for coaching education in terms of theory and research are discussed.